2007
DOI: 10.1215/15228517-2007-001
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II in the endothelium of glial tumors: A potential target for therapy

Abstract: Carbonic anhydrase isozyme II (CA II) is a cytosolic enzyme that is highly expressed in most organs, including the brain, where it is mainly located in the oligodendrocytes. Recent studies have shown that its expression is induced in the endothelium of neovessels in melanoma and esophageal, renal, and lung cancer. Immunological studies further indicate that CA II represents a major target antigen stimulating an autoantibody response in melanoma patients. These results prompted us to investigate endothelial CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 16 publications
1
47
2
Order By: Relevance
“…This result makes CA VII another CA isozyme with a significant correlation to the patient survival. Indeed, the previous studies have demonstrated that CA II, CA IX and CA XII all show similar trends as prognostic markers in diffuse astrocytomas [6,7,25,39]. The presence of several CA isozymes in astrocytomas may reflect the rapid turnover of acid metabolic products in highly malignant tumor tissues.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This result makes CA VII another CA isozyme with a significant correlation to the patient survival. Indeed, the previous studies have demonstrated that CA II, CA IX and CA XII all show similar trends as prognostic markers in diffuse astrocytomas [6,7,25,39]. The presence of several CA isozymes in astrocytomas may reflect the rapid turnover of acid metabolic products in highly malignant tumor tissues.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have indicated that carbonic anhydrase isozymes, CA II, CA IX and CA XII, are promising biomarkers for certain tumors [6,7,22,26]. There are numerous reports showing that CA IX acts not only as a marker for particular tumors, but its presence also correlates to prognosis in several tumor categories, such as brain tumors, sarcomas, and renal, lung, rectal, bladder, oral, breast, and cervical carcinomas [7,[27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human CAII gene, which locates at chromosome 8q22, codes a cytoplasmic protein that has the highest turnover rate and widest tissue distribution among the known human CA isozymes [3] . CAII is correlated with several types of tumors [9][10][11][12] . In our previous study, the expression of CAII was down-regulated in GC [2] .…”
Section: Introductionmentioning
confidence: 99%